A imputação objetiva pelas lesões permanentes e óbitos nos acidentes de trabalho - Renner, Silvio Inácio (My University, 2014)
This research is built in a combination with the analytic and dialetic methods. It has the approach directed to a discussion of charging criminal objective and his tipificacion, for the cases of permanent injuries and deaths in work accidents. The general objective was to argue the pertinent doctrine and the legislation to the environment of the work in the fields of the civil and warfare area, therefore, from the specific conceptualization of the behaviors, to verify the objective imputation of the responsibilities for the occurrence of the harmful events in the work environment. In this sense this research is based on the principle of risk through the theory of the allowed risk and the forbidden risk. And it complements the theory of increased risk to objectively discuss the allocation of responsibilities of occupational accidents and employment-related accidents to the administrator.
Esta pesquisa se caracteriza, em termos metodológicos, na combinação dos métodos, analítico e dialético. Tem o enfoque voltado à discussão da imputação objetiva penal e sua possível tipificação, para os casos de lesões permanentes e óbitos nos acidentes de trabalho. O objetivo geral foi discutir a doutrina e a legislação pertinentes ao ambiente do trabalho nos campos da área civil e previdenciária, para, a partir da conceituação específica das condutas, verificar a imputação objetiva das responsabilidades pela ocorrência dos eventos danosos no ambiente do trabalho. Neste sentido esta pesquisa apóia-se no princípio do risco, através da teoria do risco permitido e do risco proibido. E se complementa na teoria do aumento do risco para discutir pela imputação objetiva das responsabilidades dos acidentes do trabalho ao administrador e de seus órgãos.
Keywords: Direito do trabalho; Teoria da imputação objetiva; Acidentes do trabalho; Lesões permanentes e óbitos no trabalho; Responsabilidade civil objetiva; Teoria do risco; Responsabilidade no ambiente do trabalho; Legislação previdenciária; Responsabilidade penal; Periculosidade; Theory of objective allocation; Employment-related accidents; Permanent injuries and deaths at work; Objective civil liability; Theory of risk; Responsibility in the work environment; Social security legislation